Analysis of Socio-Economic Factors in Crime Dynamics in the Sumatra Region - Moch Hardi Padmanegara; Wenny Restikasari (Universitas Negeri Surabaya, 2026)
This study analyzes the influence of social factors such as population density and economic factors such as poverty and open poverty levels on crime in ten provinces in Sumatra during the period 2020–2024 using secondary data from the Central Bureau of Statistics (BPS) and the Fixed Effect Model (FEM) panel data regression method. The results show that population density has a positive and significant effect on crime, while poverty and poverty have no significant effect. The implications of this study emphasize the importance of multidimensional policies through population growth management, labor market interventions for at-risk youth, more targeted social protection, community-based law enforcement, and cross-agency data system integration to support inclusive and sustainable development in Sumatra.